Cost Optimization and Analysis for Product Launch in US Market - Balan, Prasad (Digital Repository of Theses, 2026)
This paper examines the main driving forces for cost optimization when launching generic pharmaceutical products in the USA, taking into account technological and market aspects. These include the increased pressure from competition, tighter regulations within many of industries in which we operate and changing standards in market landscapes to name a few. Components like Active Pharmaceutical Ingredients (API), Excipients, packaging components & facility management are analysed for influencing the product cost. Based on analysis of market trends, pricing pressure and generic drug commercial viability in different therapeutic categories using data from Intercontinental Marketing statistics we can learn a lot about what works (and more importantly, what doesn’t) from case studies of successful and failed product launches. The results show that strategic procurement of raw materials, efficient management of supply chains and scrupulous hygiene during manufacture are essential to cost-effectively launching sustainable products. The study uses the correlation of technical capabilities with commercial strategies to give a complete approach for cost reduction and enhancing competition among generic products in the market position. The recommendations made in this study are beneficial for manufacturers to successfully and economically launch their generic product, hence contributing to the field of pharmaceutical industry.